Pengaruh Sosial Media Marketing Facebook Terhadap Minat Sewa Konsumen Dengan Consumer Behavior Sebagai Variabel Intervening (Studi Kasus Pada Konsumen Sound System Si Doel Pasuruan) - Muchamad Agus Setiawan; Nurhajati Nurhajati; Muhammad Ridwan Basalamah (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract The development of the music industry (Sound System) in the East Java area is currently progressing very busy, especially in the Pasuruan Regency area. The increasing number of events and celebrations in Pasuruan district has led to an increasing demand and interest in the sound system. This can lift the sound system rental business into a fairly large business opportunity and is popular with many people, both young and old. Based on several advantages of Facebook social media, many marketers are optimizing the role of Facebook to influence consumer behavior in intending to rent a sound system, because the operation is very easy and many use Facebook social media to upload news or get news regarding a celebration event or do sound checks with order model that is skyrocketing or much-loved at this time. In Si Doel's sound system, apart from doing direct marketing or putting up banners in front of his house, they also use Facebook social media to post some activities or create stories on Facebook, so that it becomes a place to market their sound system business. This research uses an explanatory type of research with a quantitative approach. The results of this study are that social media marketing facebook has a positive and significant effect on consumer rental interest, social media marketing facebook has a positive and significant effect on consumer behavior on consumers, there is no influence of consumer behavior on consumer rental interest, there is a negative influence of social media marketing facebook on consumers. consumer rental interest through consumer behavior on the sound system consumer of Si Doel Pasuruan.Keywords : Sosial Media Marketing Facebook, Minat Sewa Konsumen, Consumer Behavior.